Egúngún Festival in Ìdó-Àní, South-West Nigeria - O̩laiya Oluwatoyin M.; Ọlọfinṣao Oluke̩mi M. (International Journal of Culture and History, 2024)
Much work had been carried out on the traditional festivals and traditions of Yorùbá people. However, sufficient attention had not been given to traditional festivals in Ò̩sé̩ area of Ondo State, Southwest Nigeria. This study, therefore, explores Egúngún festival among the Ìdó-Àní people. The work examines the socio-cultural significance of the festival, its relationship with traditional structures of the community as well as what extent modern change has corroded the festival. This work relies much on field work and the theoretical framework is based on the sociological approach which deals with culture of the society. The study reveals that the festival not only strengthens the bond among the quarters in the community; it also indicates that Ìdó-Àní people did not allow modernization and foreign religion to eradicate their cultural values and identity. The study also shows the aesthetics and didacticism of oral performances and expands our understanding of traditional festival in this part of Yorùbá land.